2022
DOI: 10.1155/2022/3704494
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Personalized Scenic Spot Recommendation Algorithm Based on Generalized Regression Neural Network for 5G Smart Tourism System

Abstract: On the basis of the analysis of the evolution dynamics and the process of smart tourism service, this paper constructs the evolutionary game model of smart tourism service and reveals the evolution mechanism of smart tourism service based on the network platform. Based on the strategic main line of “advantages,” it proposes the design ideas and overall framework of the smart tourism service model based on the network platform, including the smart tourism information interactive service model, the element colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…4.6.6. Superiority of the Proposed Algorithm Through analysis, it can be concluded that the proposed algorithm has significant advantages over the methods used in the literature [5][6][7][8][9][10][11][12] and the commonly used electronic map methods used in tour route planning, as follows:…”
Section: Analysis Of the Comparison Of Three Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…4.6.6. Superiority of the Proposed Algorithm Through analysis, it can be concluded that the proposed algorithm has significant advantages over the methods used in the literature [5][6][7][8][9][10][11][12] and the commonly used electronic map methods used in tour route planning, as follows:…”
Section: Analysis Of the Comparison Of Three Methodsmentioning
confidence: 99%
“…This method finally improved the collaborative filtering algorithm's performance and increased the recommendation accuracy. Lin [6] proposed a depth CTR recommendation model based on the gradient lifting tree and factor decomposer, which improved the performance of the recommendation system. Pacheco et al [7] brought forward a deep-learning recommendation system on scenic spots based on the Internet of Things and improved the system's performance.…”
Section: Analysis Of Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Tourism data mining provides various strategies and techniques to ensure the safety and security of users while traveling. The data mining process improves the communication services for the tourists that reduce the latency rate in the searching process [ 8 ]. Tourism filtering is a process that delivers travel information to tourists.…”
Section: Introductionmentioning
confidence: 99%